Estimation of landslide pressures in slope stability calculations - D. N. Gorobtsov; I. K. Fomenko; M. A. Novgorodova; O. N. Sirotkina (Известия высших учебных заведений: Геология и разведка, 2022)
Background. When developing anti-landslide measures during construction on unstable slopes, an assessment of the degree of their stability should be carried out first. When using analytical (conventional) [19] calculation methods, such an assessment is conducted by calculating the stability coefficient (Ks ), which is characterised by the ratio of forces and/or moments holding the soil massif on an inclined surface to the forces shearing this massif.Aim. Within the framework of Soviet and, further, Russian practice, anti-landslide measures are commonly developed based on determination of the magnitude of landslide pressures. However, with the introduction of foreign methodological approaches and respective software applications into the practice of slope stability calculations, the question arises whether these applications can be used for determining landslide pressures and what additional approaches exist for calculating and justifying engineering protection structures on landslide and landslide-prone slopes.Materials and methods. The main conclusion of the study is the inexpediency of using the method proposed by G.M. Shakhunyants and the inadmissibility of using limit equilibrium methods to calculate landslide pressures when designing engineering protection structures.Results. The best option for calculating such tasks is to use an extended method of marginal equilibrium. However, this approach is practically not used in Russian practice. Alternatively, we can recommend an analysis of the deficit of retaining forces based on the methods of marginal equilibrium (referred to as reverse analysis in foreign terminology).